Prevalência de HPV e seus Fatores de Risco em Adolescentes e Mulheres Jovens - Ferreira, Maria Diva Paz de Lima (2005)
Background: Human papillomavirus (HPV) infections are among the most important sexually transmitted diseases and are also considered a significant source of morbidity and mortality world wide, because of their etiological association with a variety of anogenital cancers. Estimates of HPV prevalence are extrapolated from epidemiological studies measuring current infection and vary by the population studied. The last decade has seen a significant increase in our knowwledge about HPV infections and its risk factors in adolescents. Several studies have reported that certain behavioral and biological risk factors are associated with this disease. HPV is so common and transmissible that having just one sexual partner often results in infection, therefore nearly all sexually active adolescents are at high risk for acquiring HPV. Studies of prevalence are important nowadays on the onset of vaccination programs for this population. Objectives: To determine the prevalence of HPV and analyse the demoghrafic, behavioral and biological risk factors associated to this infection, in an urban population of young students in Niterói, Rio de Janeiro. Methods: This study included 257 health adolescents and young women, sexually active, aged 14 to 26 years. The population sample was recruted from public schools in Niterói in 2004-2005. Subjects were excluded if they had a prior history of genital warts or an abnormal Papanicolaou smear. All subjects completed a self administered questionnaire regarding their demographic, comportamental, sexual and ginaecological history. A smear for cytologic examination was obtained and Human papillomavirus DNA was detected by the polymerase chain reaction (PCR) using consensus primers (MY09/11). Videodigital colposcopy with image capture, was also performed in all subjects. Results: The overall prevalence observed in our sample was 31,9%. An increased risk of HPV infection was significantly associated to withdrawal on the last intercourse (OR=3.00; CI 95% 1.13-7.92), alcohol consumption before sexual relations (OR=2,17; CI 95% 1,14-4,14), co-infection with trichomonas (OR=11.80; CI 95% 3.29- 42.38), and cervical ectopy (OR= 6.38; CI 95% 3.50-11.63). Logistic regression multivariated analysys demonstrated that the presence of ectopy, co-infection with trichomonas, and withdrawal on the last intercourse, remained as independent risk factors for HPV infection. Conclusions: Subjects with cervical ectopy and positive for trichomonas on citology were six and twelve times more likely to have an HPV infection respectively.These data are not very common on studies regarding this population, so further attention must be paid on these variables in oncoming studies to corroborate these findings. These data suggest that factors such as increased biologic vulnerability may play a role in HPV infections among adolescents and these findings may have important implications for primary prevention of HPV induced lesions.